Estimation of irreversible damageability at fatigue of carbon steel - Vakulenko, I. O.; Perkov, O. N.; Knapinski, M.; Bolotova, D. M. (Science and Transport Progress, 2014)
Purpose. Damageability estimation of carbon steel in the conditions of cyclic loading. Methodology. The steel fragments of railway wheel rim and rail head served as material for research with chemical composition 0.65 % С, 0.67 % Mn, 0.3 % Si, 0.027 % P, 0.028 % S и 0.7 % C, 0.82 % Mn, 0.56 % Si, 0.025 % P, 0.029 % S accordingly. The microstructure of tested steels corresponded to the state of metal after a hot plastic deformation. The fatigue research was conducted in the conditions of symmetric bend using the proof-of-concept machine of type «Saturn-10». Full Wohler diagrams and the lines corresponding to forming of sub-and micro cracks were constructed. The distribution analysis of internal stresses in the metal under cyclic loading was carried out using the microhardness tester of PMT-3 type.Findings. On the basis of fatigue curves for high-carbon steels analysis the positions of borders dividing the areas of convertible and irreversible damages were determined. The article shows that with the growth of carbon concentration in the steel at invariability of the structural state an increase of fatigue limit is observed. At the same time the acceleration of processes, which determine transition terms from the stage of forming of submicrocracks to the microcracks occurs. The research of microhardness distribution in the metal after destruction confirmed the nature of carbon amount influence on the carbon steel characteristics. Originality. Regardless on the stages of breakdown site forming the carbon steels behavior at a fatigue is determined by the ration between the processes of strengthening and softening. At a cyclic loading the heterogeneity of internal stresses distribution decreases with the increase of distance from the destruction surface. Analysis of metal internal restructuring processes at fatigue loading made it possible to determine that at the stages prior to incubation period in the metal microvolumes the cells are already exist with inhomogeneous position of crystalline structure defects and, primarily, dislocations. Practical value. Increase of carbon content from 0.65 to 0.7%, in the conditions of cyclic loading of steel with the structure of lamellar pearlite is accompanied by the fatigue durability increase approximately on 40%. The increase of carbon content in steel accelerates transition from the stage of forming the convertible damages of internal structure to irreversible ones that is confirmed by the increase of angular coefficient of French curves.